Praktik Pembiasaan Shalat Dhuha dalam Membentuk Karakter Religius Peserta Didik di MTS Al-Islam Kemuja - Islamiah, Robiatul; Noor, Wahyudin (LENTERNAL: Learning and Teaching Journal, 2022)
This research aims to find out: 1) The implementation of the practice of Dhuha prayer in MTs Al-Islam Worship, 2) How the efforts of the formation of the religious character of the students through the practicing of dhahah prayer at MTs al-Islam worship The type of research used is qualitative-descriptive. data and data sources that use primary and secondary data sources. Data collection techniques include observations, interviews, documentation, data analysis techniques through data reduction, data presentation, and decision-making. The results of the study showed that: 1) the implementation of the practice of the prayer of Dhuha in MTs Al-Islam Kemuja consists of aspects: a) discipline in performing the prayer of Dhuha; b) consistency of the execution of the prayers of Dhuha; c) reward and punishment; and d) prayer carried out without coercion. 2) the attempt to form the religious character of the student through the practice of prayer Dhaha can be done in such a way as: (a) the principle of freedom is the formation of the religious character the student carries out in a gradual manner; (b) the continuity principle is the formation of the religious personality the student participates in continuously; (c) the momentum principle is that the formation of the character of a student is done at a moment such as the activity of praying dhaha as a function of training in forming religious characters the student, (d) The principle of motivation instructive is the development of the religious character the participant carries on with the intention of learning the student himself; (e) the orientation is the character formation of a person by a religious supervisor. And the result obtained from the formation of the religious character of the students through the practice of the prayer is that the students become accustomed to praying one of their prayers in a routine, their fear and belief in God are increasing, they are more agamistic, they have a good nature, and they become muslims.